Challenges Associated with the Awareness and use of Electronic Journals by Faculty Members of Tertiary Institutions in Sokoto State - Suleiman, , A. Y. (Kashere Journal of Education, 2021)
The study investigated challenges associated with the awareness and use of electronic journals by faculty members in tertiary institutions of Sokoto State. In spite of the relevance of e-journals, a field survey had shown that faculty members in tertiary institutions of Sokoto State often encounter serious challenges in their effort to use electronic journals for teaching, learning and research activities. The study uses survey research design covering eight (8) tertiary institutions in Sokoto State. Questionnaire was used as the instrument for data collection and administered to 329 faculty members. The data collected were analysed, using frequencies and percentages. Findings from the study revealed unstable power supply; inadequate ICT infrastructure; poor technical skills among others as the major challenges confronting faculty members in using electronic journals in the tertiary institutions of Sokoto State. Recommendations made include the need for the institutions to improve the supply of electricity across the campuses by providing adequate, steady, constant and uninterrupted power supply as well as the provision of ICT infrastructure in the institutions.